Batik Project for Students with Special Needs to Strength Culture and Suport SDGs - Irvan, Muchamad; Wardani, Cyntia Cakra; Sunandar, Asep; Rofiah, Khofidotur (Angstrom Centre of Education, 2026)
The Pancasila Student Profiles Strengthening Project, or P5, is a government policy realized through various school projects to instill a good culture in students. This study aims to describe the implementation of P5 for students with special needs. The project carried out is making Batik. This research lasted two months (following the project agenda) at the Sumber Dharma Special School for the junior high school level. The sub-focus in this study includes planning, implementation, evaluation, and party involvement. This research uses a qualitative and descriptive approach with data collection techniques of interviews, observation, and documentary. The results of this study indicate that: 1) Planning for P5 includes forming a team of facilitators, identifying the level of readiness of education units, designing dimensions, themes, and time allocations, and compiling modules; 2) Project Implementation, including project education, practical implementation, and final project exhibition; 3) Evaluation of P5, carried out to determine the project achievement by looking at student's daily activities and reflections on each class; 4) Involvement of parties, which is carried out by collaborating with parents in approving the project activities at the planning stage, and parental support. The supporting factors in implementing P5 are customized planning, a grouping of students, teachers as facilitators, peer tutors, and parents. Meanwhile, the inhibiting factor during the implementation of P5 lies in the limited practice space and inappropriate implementation time.